Antioxidant activity of phenolic compounds from extracts of Eucalyptus globulus and Melaleuca styphelioides and their protective role on D-glucose-induced hyperglycemic stress and oxalate stress in NRK-49Fcells. Issue 11 (3rd June 2018) - Ganesan, Divya; Al-Sayed, Eman; Albert, Abhishek; Paul, Eldho; Singab, Abdel Nasser B.; Govindan Sadasivam, Selvam; Saso, Luciano
Abstract: Phytochemicals serve as potential therapeutic agents for the prevention and treatment of diseases. In this study, we elucidate the renoprotective activity of compounds isolated from Eucalyptus globulus and Melaleuca styphelioides extracts in glucose- and oxalate-challenged NRK-49F cell model. The antioxidant potential of isolated compounds was evaluated based on their effect on antioxidant enzyme activities and lipid peroxidation levels. The results demonstrated that exposure of NRK-49F cells to glucose and oxalate stress augmented cell damage and attenuated antioxidant enzyme activities. The phytochemicals 2, 2, 8-trimethyl-6-formyl-chrom-3-ene-7- O -β-D-glucopyranoside, Cornusiin B and tellimagrandin I treatment restored antioxidant enzyme activity, significantly lowered lipid peroxidation levels and effectively protected cells from glucose and oxalate stress equivalent to the known antioxidant, N -acetyl cysteine. Pterocarinin A significantly reversed cellular damage owing to glucose stress. In conclusion, the compounds isolated from E. globulus and M. styphelioides showed potential cytoprotective and anti-oxidative property against glucose- and oxalate-induced oxidative stress in NRK-49F cells. Abstract :